Upgrading ethanol to 1-butanol with a homogeneous air-stable ruthenium catalyst. Issue 14 (13th January 2016) - Tseng, Kuei-Nin T.; Lin, Steve; Kampf, Jeff W.; Szymczak, Nathaniel K.
Abstract : An amide-derived N, N, N -Ru(ii ) complex catalyzes the conversion of EtOH to 1-BuOH with high activity. Abstract : An amide-derived N, N, N -Ru(ii ) complex catalyzes the conversion of EtOH to 1-BuOH with high activity. Conversion to alcohol upgraded products exceeds 250 turnovers per hour (>50% conversion) with 0.1 mol% catalyst loading. In addition to high activity for ethanol upgrading, catalytic reactions can be set up under ambient conditions with no loss in activity.